The natural reservoirs of Mycoplasma gallisepticum - Обуховська, О. В. (Scientific Progress & Innovations, 2012)
It has been proved that decorative and wild bird may be the natural reservoir of Mycoplasma gallisepticum. It has been provided that content for the limited territory of birds of different species of parasite transmission occurs from the typical (chickens, turkeys, pheasants) to the unusual (ducks, geese, swans). The seropositivity among waterfowl can reach values of 12.73 %, the mikoplazmacarrier – 5.45 % of the total population. It was revealed that in populations of wild waterfowl (ogarej) up to 17 % of individuals are potential mikoplazmacarriers.